MOBILE PHONE AS A SOURCE OF ARTIFICIAL EXPOSURE OF ELECTROMAGNETIC FIELDS ON THE POPULATION - A. N. Liberman; S. G. Denisov (Радиационная гигиена)
The paper presents characteristics  of the main sources of artificial exposure of electromagnetic fields on the population. Particular attention is drawn to the means of mobile telecommunication that became commonplace in the world, mobile and cordless (home) phones.